Revelation Principle with Persistent Correlated Types: Impossibility Result - Suehyun Kwon (Center for Economic Studies and ifo Institute (CESifo), 2019)
Abstract
Keywords: D82; 330; mechanism design; limited commitment; revelation principle; informed-principal problem; persistence; correlated types